Adaptive technologies for the blind and visual impaired persons in the traffic network - Periša, Marko; Peraković, Dragan; Vaculík, Juraj (Transport, 2015)
The information about the environment and the precise guidance of visually impaired people is the basis for their safe movement of the traffic network. Therefore, the information and communication services should be adapted to this group of users. The services based on the advanced information and communication technologies provide the visually impaired persons with information about the environment while moving along the traffic network. This paper analyses the currently available information systems of users when moving traffic network, and the currently most services based on new ICT (Information and Communications Technology). The analysis was carried on a representative sample of the City of Zagreb (Croatia) in involving all interest groups of visually impaired people. Based on defined user requirements is proposed a new services based on NFC (Near Field Communication) and RTLS (Real-Time Locating Systems). Testing and analysing the efficiency of single information and communication technologies have been performed on the actual traffic network system of the City of Zagreb. The users of the Croatian Society for Promotion and Development of Tiphlotechnology (Hrvatska Udruga za Promicanje i Razvoj Tiflotehnike – HUPRT, http://www.huprt.hr) participated in checking the efficiency of single technologies and services. First published online: 28 Jan 2015